A preliminary analysis of non-accounting students perception towards introductory accounting course among private institutions in Sabah - Mohd Allif Anwar Abu Bakar; Sharifah Milda Amirul; Noraizan Ripain; Nur Shahida Ab Fatah; Mathew Kevin Bosi (Penerbit UMS, 2019)
The introductory accounting course is mostly covered at undergraduate level as one of the core courses in many business degree programmes for both public and private institution in Malaysia. This research came to the attention of the researcher due to the students’ poor performance, repeats and pre-conceive accounting as difficult and unattainable. The aim of this paper is to examine the perception of non-accounting students in introductory accounting course among private institution. A study was carried out covering 244 students from 8 different private institution in Sabah. The study focused mainly on aspects of program structure, assessment and external factor. Our preliminary descriptive findings suggest that the criteria of program structure have no effect towards their perception of introductory accounting course. Meanwhile for the assessment factor, time allocated during final examination, assessment which need to be matched with the course outcome and marks allocated address no impacts against their perceived perceptions. Yet, a small number of students strongly agree with the statement that the language/terms used in the questions are not understandable, the format of exam question do not consistent with the past year exam and exam questions are not clearly structured. External factors of family, facilities, transportation and relationship problems revealed no importance. The non-accounting student perceived these external factors to be insignificant in influencing their decision whether accounting course is acceptable or not in their learning environment. However, a big number of students perceived financial problems to be an important factor. Finally, results revealed that students are generally still in favour with the assessment and program structure of introductory accounting course.